Hair Shedding Evaluation for Alopecia: A Refined Wash Test - Li X; Wang X; Wang C; Zhang J; Zhou C (Dove Medical Press, 2022)
Xiangqian Li, Xianghe Wang, Chen Wang, Jianzhong Zhang, Cheng Zhou Department of Dermatology, Peking University People's Hospital, Beijing, People's Republic of ChinaCorrespondence: Cheng ZhouDepartment of Dermatology, Peking University People's Hospital, No. 11 Xizhimen South Street, Xicheng District, Beijing, 100044, People's Republic of China, Email chengzhou@live.cnPurpose: The aim of this study is to establish a refined wash test (RWT) and explore the characteristics of daily shedding hair parameters in normal individuals and patients with androgenetic alopecia (AGA) or telogen effluvium (TE).Materials and Methods: Chinese subjects diagnosed as normal, AGA or TE were enrolled. For the RWT procedure, the subjects were asked to pre-wash their hair 24 hours before the first collection, then to wash and rinse their hair with flowing water above a sink covered with a piece of filtering cloth. All hairs entrapped in the filtering cloth were air dried and collected. This "wash-and-collect" process was repeated for 3 consecutive days with a 24 ± 2 hour interval. Collected hairs were counted manually, and hair diameter was measured by videodermoscope. Number and diameter of daily shedding hairs and percentage of vellus and terminal hairs were analyzed.Results: A total of 176 subjects participated in and completed the study. Shedding hair number during daily shampooing was 27.9 ± 12.2, 52.2 ± 28.5 and 125.5 ± 62.7 hairs in normal, AGA and TE participants, respectively, and the differences between each two of the three groups were all statistically significant. Diameter of shedding hairs was 76.9 ± 9.0 μm, 60.0 ± 9.5 μm and 82.7 ± 9.2 μm in normal, AGA and TE, respectively. Along with advancement of AGA severity, shedding hair number was generally increased, while hair diameter decreased. The percentage of vellus hairs in AGA was significantly higher than in the normal and TE groups (8.3 ± 6.6% vs 1.0 ± 1.6% and 1.0 ± 1.0%). The combination of shedding hair number and percentage of vellus hairs had a high diagnostic confidence (AUC = 0.957) to diagnose AGA from normal. Shedding hair number alone showed high confidence to diagnose TE from normal (AUC = 0.999).Conclusion: The non-invasive, easy-to-use RWT established in this study is a valuable tool to evaluate daily shedding hairs, which may be useful in diagnosis, dynamic monitoring of disease progression and treatment efficacy.Keywords: hair loss, hair shedding, refined wash test, androgenetic alopecia, telogen effluvium